2022
DOI: 10.3390/foods11193108
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Phenolic Component Bioavailability Using the In Vitro Digestion/Caco-2 Cell Model, as well as the Antioxidant Activity in Chinese Red Wine

Abstract: Red wine is a well-known alcoholic beverage, and is known to have phenolic compounds (PCs), which contribute to its antioxidant activity and have other beneficial advantages for human health. The aim of this study was to evaluate the effect of the simulated gastro-intestinal digestion and the Caco-2 transepithelial transport assay on the PCs, bioavailability, and the antioxidant capacity of red wines. The contents of PCs in red wine were significantly reduced during most of the digestion phases. Phenolic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Besides, Wu et al [ 16 ] reported that the absorption of caffeic acid was higher than chlorogenic acid in the Caco-2 model as well as in rat jejunum. Therefore, the use of an in vitro digestion/Caco-2 cell culture model has been proposed by several authors as an economical and useful alternative to the in vivo analysis, in order to investigate the bioavailability of phenolic compounds [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Wu et al [ 16 ] reported that the absorption of caffeic acid was higher than chlorogenic acid in the Caco-2 model as well as in rat jejunum. Therefore, the use of an in vitro digestion/Caco-2 cell culture model has been proposed by several authors as an economical and useful alternative to the in vivo analysis, in order to investigate the bioavailability of phenolic compounds [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability of the aforementioned compounds is a key issue as it affects their biological function. In general, wine phenolic compounds are only partially bioavailable, not only because of their chemical structure but also due to the biotransformations that take place during digestion [110]; it has been reported to range between 2-25% [111][112][113].…”
Section: Functional Properties Of Winementioning
confidence: 99%
“…The most commonly studied biological activities include antioxidant, vascular function, antiproliferative, antimicrobial, and anti-inflammatory effects. The MKN-28 (gastric cell) and Caco-2 (intestinal cell) cells have been frequently used, simulating the gastric and intestinal environments, respectively [52][53][54][55], while VSMC (vascular smooth muscle cells) and HUVECs (human umbilical vein endothelial cells) have been used to study vascular function [56][57][58]. Other cells such as HepG2 (human liver cancer cell), BRL-3A (rat liver cell), SH-SY5Y (human neuronal cell), and prostate cancer cells are being used to assess the antiproliferative and anticancer effects of anthocyanins [59,60].…”
Section: Bioavailability: Definition and Study Designsmentioning
confidence: 99%
“…It has been well-documented in the literature that anthocyanins inherently possess antioxidant properties, as evident from several in vitro studies where they consistently exhibit antioxidant efficacy irrespective of their form-whether purified, in crude extracts, or within whole foods [54,[58][59][60]78,94]. These studies, summarised in Table 1, predominantly employ cell models to assess antioxidant activity.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
See 1 more Smart Citation